2016
DOI: 10.1016/j.ijmm.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Role of a sensor histidine kinase ChiS of Vibrio cholerae in pathogenesis

Abstract: Vibrio cholera survival in an aquatic environment depends on chitin utilization pathway that requires two factors, chitin binding protein and chitinases. The chitinases and the chitin utilization pathway are regulated by a two-component sensor histidine kinase ChiS in V. cholerae. In recent studies these two factors are also shown to be involved in V. cholerae pathogenesis. However, the role played by their upstream regulator ChiS in pathogenesis is yet to be known. In this study, we investigated the activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 35 publications
(44 reference statements)
0
24
0
Order By: Relevance
“…cholerae OMV specific antibody significantly reduce adherence by inhibiting V . cholerae motility [ 82 ]. So, our data indicate that our immunogen also induced protective immune response by blocking initial bacterial entry via intestinal epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…cholerae OMV specific antibody significantly reduce adherence by inhibiting V . cholerae motility [ 82 ]. So, our data indicate that our immunogen also induced protective immune response by blocking initial bacterial entry via intestinal epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Mucin also activates the two-component sensor histidine kinase ChiS in V. cholera . ChiS is the regulator of the chitinases and the chitin utilization pathway, but also plays a role in the virulence of the bacteria since the mutant strain is hypovirulent (Chourashi et al, 2016 ). Released monosaccharides from mucin O-glycans degradation can also act as a chemical cue to help pathogens to sense their environment and adapt accordingly.…”
Section: Role Of Mucin Components In Modulation Of Bacterial Virulencmentioning
confidence: 99%
“…Reports have also indicated the involvement of bacterial chitinases in pathogenesis [9][10][11]. Our studies have shown that the chitinase ChiA2 (VCA0027) is important for V. cholerae survival and pathogenesis [11,12].…”
mentioning
confidence: 72%
“…ChiS also promotes motility, mucin-layer penetration, adherence and survival in the intestinal environment. Moreover, ChiS mutant V. cholerae shows hypovirulent characteristics as it secretes less cholera toxin (CT) in the intestine, and hence shows less fluid accumulation and less virulence [12].…”
mentioning
confidence: 99%